Police Sector Design Incorporating Preferences of Interest Groups for Equality and Efficiency - Bodily, Samuel E. (Management Science, 1978)
This paper proposes and illustrates by example a decision model for a resource allocation problem in urban management—the design of service areas for police mobile units. Estimates of the performance of alternative designs are given by existing analytic models of spatially distributed emergency service systems. Using multiattribute utility theory, alternatives are evaluated according to the preferences for efficiency and equality of service of three interest groups: citizens, police, and administrators. Meaningful measures of inequality are developed and an algorithm is created for generating improved sector designs.